2004
DOI: 10.1258/0969141042467403
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific interval breast cancers in New South Wales and meta-analysis of studies of women aged 40–49 years

Abstract: Objective:To compare interval cancers in the 40-49 year age group with other age groups in New South Wales and with published trials and service studies.Setting: New South Wales data were derived from the population-based biennial mammography screening program, which achieved state-wide coverage in 1995. Women aged 40-49 years screened during 1995-1998 were included. Methods:Bilateral two-view mammography with reading by two radiologists was employed for biennial screening examinations. Interval cancers were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Higher IC rates in younger women were reported by one group (Taylor et al, 2004) although other studies have not confirmed this finding (Fracheboud et al, 1999). The reasons for this variability are difficult to identify, but it is likely that the low number of cancers in our study makes it difficult for us to provide conclusive evidence about this question.…”
Section: Discussioncontrasting
confidence: 54%
“…Higher IC rates in younger women were reported by one group (Taylor et al, 2004) although other studies have not confirmed this finding (Fracheboud et al, 1999). The reasons for this variability are difficult to identify, but it is likely that the low number of cancers in our study makes it difficult for us to provide conclusive evidence about this question.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in the I-SPY 1 cohort, even after adjusting for age, the actual rate of ICs (85%) for women presenting with a large, rapidly growing tumor far exceeded the expected rate of 32%. This difference appears to be due to differences in the biology of tumors that present as palpable masses compared with screen-detected tumors [811, 22, 24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…13 We could only locate two meta-analyses of interval cancers. 16,19 A reason for that could be the lack of standardized methods and proper data. Taylor and co-workers' meta-analysis of interval cancer incidence in randomized controlled trials and service screening programmes for women aged 40-49 showed that the proportionate incidences of the first-, and second-year interval cancers were 42% and 63% in the randomized controlled trials and 44% and 72% in the service screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor and co-workers’ meta-analysis of interval cancer incidence in randomized controlled trials and service screening programmes for women aged 40–49 showed that the proportionate incidences of the first-, and second-year interval cancers were 42% and 63% in the randomized controlled trials and 44% and 72% in the service screening programmes. 16 However, the studies included were, except for the New South Wales (NSW)-study (606 out of 1305 cases), small and followed-up for only two years which makes the interpretation difficult. Anyhow, our adjusted figures for the ages 40–49 were considerably lower than the corresponding figures for NSW (48% vs. 56% for early and 54% vs. 86% for late interval cancer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation